DESAIN SISTEM INFORMASI PEMASARAN BERBASIS WEB PADA USAHA KERAJINAN ANYAMAN BAMBU CENRAPOLE DI KABUPATEN BARRU - Tien, Sari; Arifah; Asriany (JOURNAL VISION TECHNOLOGY (V-TECH), 2024)
Along with the increasingly rapid development of technology and information, one of the ways used to disseminate information is by using websites. In marketing products such as woven bamboo, websites can be used to convey information about the products you want to market. The aim of this research is to create a web-based marketing information system design for the Cenrapole bamboo woven craft business. The method used in this research is using the SDLC method with a system design using the Unified Modeling Language (UML). The result of this research is a web application design that can be used online to market Cenrapole Bamboo Woven products in Barru Regency Keywords: Bamboo woven, SDLC, Information system, Web